ROOT AND STEM IN ENGLISH AND ARABIC LANGUAGE - Rika Lestari; retno fitriani; Dinda Nurlaili; Lutfi Nuraini Ismaiyah; Kevin Fawaizul Umam; bayu bimantara (Universitas Islam Balitar, 2017)
The root and stem are the lowest levels at which a language speificific structure can be categorized. Additional categorization is the syntac level. An empirical study comparing root and stem categorization in a sample of two languages (English and Arabic) shows far-reaching distinctions.Therefore the researchers conducted the research about root and stem in arabic and english.The research method that was used is descriptive qualitative method. To gain the data the researchers used literature review in which the data gained from dictionary,English and arabic articles.The data analysed by using content analysis.These variations in the categorization of linguistic signs at the most fundamental levels cast doubt on any thesis claiming universal categorization or stem categorization. Such a static perspective should be substituted by a vibrant perspective demanding the role of categorization in linguistic operation.